FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN MUSKULOSKELATAL PADA PEKERJA INDUSTRI TAHU DI KOTA JAMBI TAHUN 2024 - Nur Fadillah; Subakir , Subakir; Melda Yenni (Jurnal Cakrawala Ilmiah, 2024)
Complaints of musculoskeletal disorders remain a problem for tofu industry workers. This is due to non-ergonomic working positions, heavy physical loads, and high repetition of movements during the production process, which can lead to back pain, joint pain, and muscle disorders. The research aims to identify factors related to musculoskeletal complaints among tofu industry workers in Jambi City. The study utilizes a cross-sectional design, conducted at tofu factories in Jambi City from June 4 to June 13, 2024. The research sample consists of 32 tofu industry workers in Jambi City for the year 2024, selected using purposive sampling. Data analysis employs Spearman's correlation test. The results indicate that 50.0% of respondents experience moderately severe musculoskeletal complaints, 40.6% have light workloads, 84.4% have normal BMI, and 43.8% are smokers with light to moderate smoking habits. There is a significant correlation between workload (p-value=0.000) and musculoskeletal complaints among tofu industry workers in Jambi City. Factors unrelated to musculoskeletal complaints include BMI, smoking habits, and working hours. Work attitude and workload are identified as factors associated with musculoskeletal complaints among tofu industry workers.